Straight spinning cosmic strings in Brans-Dicke gravity - Dos Santos, S. Mittmann [UNESP]; Da Silva, J. M. Hoff [UNESP]; Cindra, J. L. [UNESP] (World Scientific Publishing, 2018)
An exact solution of straight spinning cosmic strings in Brans-Dicke theory of gravitation is presented. The possibility of the existence of closed time-like curves around these cosmic strings is analyzed. Furthermore, the stability about the formation of the topological defect discussed here is checked. It is shown that the existence of a suitable choice for the integration constants in which closed time-like curves are not allowed. We also study the (im)possibility of using the obtained spacetime in the rotational curves problem.
Keywords: Brans-Dicke gravity; Spinning cosmic strings